2017
DOI: 10.3391/mbi.2017.8.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Settlement plates as monitoring devices for non-indigenous species in marine fouling communities

Abstract: Experimental studies evaluating the effects of food availability on the movement of free-ranging animals generally involve food supplementation rather than suppression. Both approaches can yield similar insights, but we were interested in the potential for using food suppression for the management and control of invasive predators, in particular, the brown treesnake (Boiga irregularis) on Guam. However, understanding a species' response to food resources is critical before employing such a strategy. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…Heavy metals, such as copper, either historically or presently used in antifouling paints, can negatively impact native biodiversity (Dafforn et al, 2011;Kinsella & Crowe, 2016). Previous studies have demonstrated these contaminants can also enhance the richness and abundances of invasive species (Marraffini et al, 2017;Piola et al, 2009); thus complexity could facilitate the increase of the non-endemic species pool. Studies directly manipulating contamination inside and outside harbours would be required to establish the importance of this factor as a moderator of complexity effects.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals, such as copper, either historically or presently used in antifouling paints, can negatively impact native biodiversity (Dafforn et al, 2011;Kinsella & Crowe, 2016). Previous studies have demonstrated these contaminants can also enhance the richness and abundances of invasive species (Marraffini et al, 2017;Piola et al, 2009); thus complexity could facilitate the increase of the non-endemic species pool. Studies directly manipulating contamination inside and outside harbours would be required to establish the importance of this factor as a moderator of complexity effects.…”
Section: Discussionmentioning
confidence: 99%
“…to monitor or experimentally manipulate benthic communities (Altman and Whitlatch, 2007;Bowden et al, 2006;Féral et al, 2016;Judge and Craig, 1997;Marraffini et al, 2017;Moura et al, 2008;Piola and Johnston, 2008;Sorte et al, 2010). Although artificial structures have already been used to compare biodiversity of marine hard bottoms from distinct geographical regions, the artificial substrates varied in size and material while colonization time, processing and analytical protocols were also different, making large-scale comparisons difficult to establish.…”
mentioning
confidence: 99%
“…This included settlement arrays, crab traps, crab condos and shoreline surveillance. Each of these methods have been shown to be effective tools in IMP surveillance (Hewitt & McDonald, ; Marraffini, Ashton, Brown, Chang, & Ruiz, ; Tait & Inglis, ). For example, settlement arrays consist of a set of small plastic plates that provide vacant space upon which marine organisms can settle and grow (Figure ).…”
Section: Development Of a Collaborative Surveillance Programmementioning
confidence: 99%